2013
DOI: 10.1021/ie301178p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Particle Size of Quartz Powder on the Synthesis and CO2 Absorption Properties of Li4SiO4 at High Temperature

Abstract: Li 4 SiO 4 was obtained by using quartz powder of different particle sizes (75−180 μm, 45−75 μm, 38−45 μm, and <38 μm) and Li 2 CO 3 as raw materials through a solid-state reaction at 720 °C. X-ray diffraction (XRD), scanning electron microscopy (SEM), and differential thermal analysis and thermogravimetry (DTA/TG) were used to examine the sintering behavior and properties of the samples. The results indicated that when the particle size of the quartz powder decreased, the solid-state reaction performed more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…This distinct phase composition can be ascribed to the different physical properties of the raw materials. It was demonstrated that an increasing of SiO 2 content and the reducing of raw materials' particle size was helpful to the synthesis of Li 4 SiO 4 . Because of the fact that the pretreatment rice straw ash presented the larger amount of SiO 2 and the smaller particles size than those of the other biomass ash (Figure ), its resulting PR‐Li 4 SiO 4 sorbent was performed more completely in the solid‐state reaction and contained the higher phase purity of Li 4 SiO 4 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This distinct phase composition can be ascribed to the different physical properties of the raw materials. It was demonstrated that an increasing of SiO 2 content and the reducing of raw materials' particle size was helpful to the synthesis of Li 4 SiO 4 . Because of the fact that the pretreatment rice straw ash presented the larger amount of SiO 2 and the smaller particles size than those of the other biomass ash (Figure ), its resulting PR‐Li 4 SiO 4 sorbent was performed more completely in the solid‐state reaction and contained the higher phase purity of Li 4 SiO 4 .…”
Section: Resultssupporting
confidence: 89%
“…Various synthesis strategies such as solid‐state reactions , impregnated suspension , sol−gel method , and precipitation were considered to synthesize Li 4 SiO 4 sorbents. Meanwhile, the sources of Si including quartz , amorphous silica (SiO 2 ) , tetraethyl orthosilicate (TEOS) , and the precursors of Li involving Li 2 CO 3 , LiOH·H 2 O, LiNO 3 , and CH 3 COOLi were also examined. It was also demonstrated that the CO 2 capture performance could be improved by introducing appropriate dopants into the Li 4 SiO 4 crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction (2) was evidenced at this temperature and it is in good agreement with other reports showing that Li 4 SiO 4 is able to chemisorb CO 2 between 460 and 580 °C. 16,[23][24][25][26][27][28]34 Th e last isothermal comparison was performed at 650 °C ( Fig. 9).…”
Section: (B)mentioning
confidence: 99%
“…8 Among these materials, lithium silicates have been reported as good solid candidates for CO 2 sorbents in terms of large CO 2 sorption capacity and high operating temperatures. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Recently, Durán-Muñoz et al 22 published that lithium oxosilicate (Li 8 SiO 6 ) is able to capture CO 2 over a wide temperature range with an experimental maximum capacity of 11.8 mmol CO 2 per gram of ceramic (theoretical 16.6 mmol/g). In addition, they reported that the Li 8 SiO 6 -CO 2 mechanism depends on the reaction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Many synthesis strategies, such as solid‐state reactions 15, impregnated suspension 16, the sol‐gel method 17, 18, and precipitation 17, 19, have been developed to prepare Li 4 SiO 4 sorbents. It was demonstrated that the performance of CO 2 capture mainly depended on the nature of the starting materials, including the silicon source such as quartz 20, amorphous silica (SiO 2 ) 21, tetraethyl orthosilicate (TEOS) 17, and some environment‐friendly silicon materials (e.g., fly ashes 22, rice husk ashes 23, and diatomite 24). The precursors of Li 17, 25 involve Li 2 CO 3 , LiOH·H 2 O, LiNO 3 , and CH 3 COOLi.…”
Section: Introductionmentioning
confidence: 99%